Assessment of nutritional parameters in elderly hemodialysis patients - Muhammed Faruk Aşkın; Yener Koç (Intercontinental Journal of Internal Medicine, 2026)
Aims: Malnutrition is a common and important condition in hemodialysis patients, associated with increased mortality and morbidity. This study aimed to identify parameters that may be associated with the level of malnutrition in elderly hemodialysis patients and to determine the most reliable parameter for detecting malnutrition in the elderly hemodialysis patient population. Methods: This cross-sectional study included 136 patients aged 65 years and older undergoing hemodialysis at four centers. We evaluated sociodemographic characteristics, laboratory parameters, and comorbidities. The Controlling Nutritional Status (CONUT), Geriatric Nutritional Risk Index (GNRI), Malnutrition Inflammation Score (MIS), Subjective Global Assessment (SGA), and Normalized Protein Nitrogen Appearance (nPNA) scales were applied to assess the nutritional status of patients. Results: The mean age was 73.25±5.75 years, hemodialysis duration was 5.35±6.21 years, and body mass index (BMI) was 25.56±4.75 kg/m². Patients with a BMI below 22 kg/m² were older (p=0.035), had longer hemodialysis durations (p=0.016), and had significantly lower abdominal skinfold thickness (ASF), triceps skinfold thickness (TSF), and waist circumference (all p